Study of the rotating gliding discharge at atmospheric pressure - Chernolutsky, D.L.; Kolgan, V.V.; Chernyak, V.Ya.; Nedybaliuk, O.A.; Iukhymenko, V.V.; Shapoval, V.O.; Solomenko, O.V.; Yakimov, M.O.; Lisitchenko, T.E. (Вопросы атомной науки и техники, 2014)
The possibility of creating a source of non-equilibrium atmospheric pressure plasma based on the rotating gliding discharge is considered in this research. Systems used for the research of the rotating gliding discharge at atmospheric pressure are described. Results, obtained during the study are presented. The possibility of creating discharge system with a bigger effective area of the discharge cathode binding to electrode than standard electric arc plasma generators is demonstrated.